Sex-Dependent Association Between Early Morning Ambulatory Blood Pressure Variations and Acute Mountain Sickness - Chen, Renzheng; Yang, Jie; Liu, Chuan; Sun, Mengjia; Ke, Jingbin; Yang, Yuanqi; Shen, Yang; Yuan, Fangzhengyuan; He, Chunyan; Cheng, Ran; Lv, Hailin; Tan, Hu; et al. (Frontiers in Physiology, 2021)
Abstract Background Acute high altitude exposure elicits blood pressure responses in most subjects, and some of them suffer from acute mountain sickness. However, a 24-hour ambulatory blood pressure change and the correlation with the occurrence of acute mountain sickness in different sexes are still unclear. Objectives This prospective study aimed to investigate high altitude induced blood pressure responses in males and females and the relationship between acute mountain sickness and 24-hour ambulatory blood pressure. Methods Forty-six subjects were matched according to demographic parameters by propensity score matching with a ratio of 1:1. All the subjects were monitored by a 24-hour ambulatory blood pressure device; the measurement was one period of 24 hour blood pressure. 2018 Lake Louise questionnaire was used to evaluate acute mountain sickness. Results Both the incidence of acute mountain sickness (14 [60.9%] vs. 5 [21.7%], P=0.007) and headache (18 [78.3%] vs. 8 [34.8%], P=0.003) were higher in females than in males. All subjects showed an elevated blood pressure in the early morning (morning systolic blood pressure, 114.72±13.57 vs 120.67±11.10, P=0.013). The elevation of morning systolic blood pressure variation was more significant in females than in males (11.95±13.19 vs -0.05±14.49, P=0.005), and a higher morning blood pressure surge increase (4.69±18.09 vs -9.66±16.96, P=0.005) was observed after acute high altitude exposure in the female group. The increase of morning systolic blood pressure was associated with acute mountain sickness occurrence (R=0.662, P<0.001) and acute mountain sickness score (R=0.664, P=0.001). Among the acute mountain sickness symptoms, we further revealed that the incidence (R=0.786, P<0.001) and the severity of headache (R=0.864, P<0.001) are closely correlated to morning systolic blood pressure. Conclusions Our study demonstrates that females are more likely to suffer from acute mountain sickness than males. acute mountain sickness is closely associated with elevated blood pressure in the early morning period, which may be correlated to higher headache incidence in subjects with higher morning systolic blood pressure.